2021
DOI: 10.1111/ajt.16270
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical biliary strictures as a cause of long-term allograft dysfunction in children who underwent liver transplantation

Abstract: The long-term outcome of liver grafts in children following liver transplantation (LT) is unknown. Grafts transplanted into children are meant to survive for long time, hence a number of centers started to perform routine protocol biopsies to detect any type of graft injury at an early stage. 1 However, the focus so far has been placed on graft hepatitis and fibrosis, most likely because of immune reactions against the transplanted organ. 2 Indeed, although liver biopsy is widely considered an essential tool t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…PTC was performed in case of elevated alanine aminotransferase (ALT) or gamma glutamyl transpeptidase (GGT) and/or history of cholangitis and/or liver biopsy consistent with cholangiolar proliferation. Remarkably, in a few cases, PTC was done even in absence of biochemical abnormalities based on evidence of isolated and significant cholangiolar proliferation at liver biopsy [ 2 ]. One hour before the procedure, all patients received iv antibiotics classified into first- and second-line prophylaxis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTC was performed in case of elevated alanine aminotransferase (ALT) or gamma glutamyl transpeptidase (GGT) and/or history of cholangitis and/or liver biopsy consistent with cholangiolar proliferation. Remarkably, in a few cases, PTC was done even in absence of biochemical abnormalities based on evidence of isolated and significant cholangiolar proliferation at liver biopsy [ 2 ]. One hour before the procedure, all patients received iv antibiotics classified into first- and second-line prophylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…Biliary complications are a major source of morbidity after liver transplant (LT), and their reported incidence varies between 5 and 20% in children [ 1 , 2 ]. If properly managed, biliary complications are thought not to affect significantly patient and graft survival [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biliary atresia (BA) is the most common indication for pediatric liver transplantation 1. With advances in techniques for pediatric living donor liver transplantation (LDLT), recipient and graft survival rates have improved significantly, but biliary stricture (BS) remains an Achilles’ heel for pediatric LDLT 2–4. The incidence of BS after pediatric LDLT has been reported to be 10%–35% 2,5,6.…”
Section: Introductionmentioning
confidence: 99%
“…[1] With advances in techniques for pediatric living donor liver transplantation (LDLT), recipient and graft survival rates have improved significantly, but biliary stricture (BS) remains an Achilles' heel for pediatric LDLT. [2][3][4] The incidence of BS after pediatric LDLT has been reported to be 10%-35%. [2,5,6] Some of them were difficult to treat, and this can lead to graft loss or even death.…”
Section: Introductionmentioning
confidence: 99%
“…The suspicion and diagnosis of a biliary stricture should be clinical in the first instance, because the onset of imaging-detectable bile duct dilation may develop only in later stages or may not occur in case of fibrotic and poorly elastic liver parenchyma. Nevertheless, Sansotta et al (7) observed that biliary strictures can be clinically and biochemically silent and only incidentally detected in liver biopsies performed in the routine follow-up of orthotopic liver transplantation. The mechanisms of poor clinical manifestation of biliary strictures are not clearly understood yet; a possible hypothesis, on which we are investigating, implies that biliary drainage may be compensated through lymphatic pathways (Figure 1).…”
mentioning
confidence: 99%